ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI DARI DAUN PETAI CINA (Leucaena leucocephala (Lam.) De Wit.) - Ari Sartinah; Puji Astuti; Subagus Wahyuono (Majalah Obat Tradisional, 2010)
Plants are important natural resources widely explored for maintaining health and treatment of diseases. One of them is Leucaena leucocephala leaf which is used as traditional medicine. Indonesian has used this leaf to treat wound and inflammation. This study was conducted to isolate and identify antibacterial compounds from L. leucocephala leaves. Dry powder of this leaf was extracted using washbenzen by Soxhletation method followed by methanol extraction. Both extracts were tested for antibacterial activity against Staphylococcus aureus ATCC 25923 dan E. coli 25922 and analysed by TLC. Positive extract to S. aureus was further separated by vacuum liquid chromatography using different combination of washbenzene and ethyl acetate followed by analysis using TLC. Each fraction was tested for antibacterial activity and analysed by TLC. The positive fraction was further separated by TLC-preparative, assigned as p1a, p2a, p3a. The active compound (p2a) was tested for its purity using TLC with various mobile phase. Its structure was identified using combination data of UV-Vis and IR spectrophotometry, GC-MS and NMR.  Based on UV-Vis data, this compound showed the absence of chromophoric group.  IR data showed adsorption at 3409,4 cm-1 (OH), 2928,2 cm-1(CHaliphatic), 2854,3 cm-1(CHaliphatic), 1575,5 cm-1 (C=C), 1416,4 cm-1 (CH2), 1385,0 cm-1(CH3), 1258,3 cm-1 and 1082,3 cm-1 (C-O). GC-MS data showed molecule ion at m/z 482   (M + H+)and fragmented ion at  m/z 427   (M + H+). 1H-NMR (CDCl3) spectrum showed resonance at δ 0,8; 1,4; 1,6; 2,0; 2,3; 3,6; 4,2 and  5,4 pp, suggesting that this compound is lupeol.